68Ga-Chelation and comparative evaluation of N, N′-bis-[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N, N′-diacetic acid (HBED-CC) conjugated NGR and RGD peptides as tumor targeted molecular imaging probes. Issue 3 (2nd March 2017) - Satpati, Drishty; Sharma, Rohit; Kumar, Chandan; Sarma, Haladhar Dev; Dash, Ashutosh
Abstract : Radiosynthesis and bioevaluation of HBED-CC conjugated RGD and NGR peptides, 68 Ga-HBED-CC-c(NGR) and 68 Ga-HBED-CC-c(RGD) is described. Abstract : Peptides containing RGD and NGR motifs display high affinity towards tumor vasculature molecular markers, integrin αv β3 and CD13 receptors, respectively. In the present study, RGD and NGR peptides were conjugated with the novel acyclic chelator N, N ′-bis-[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine- N, N ′-diacetic acid (HBED-CC) for radiolabeling with 68 Ga. The radiotracers [ 68 Ga-HBED-CC-c(NGR)] and [ 68 Ga-HBED-CC-c(RGD)] were quite hydrophilic with respective log  P values being −2.8 ± 0.14 and −2.1 ± 0.17. 68 Ga-HBED-CC-c(RGD) displayed a significantly higher ( p < 0.05) uptake in murine melanoma B16F10 tumors as compared to 68 Ga-HBED-CC-c(NGR) indicating its higher specificity towards integrin αv β3 -positive tumors. The two radiotracers showed similar uptake in CD13-positive human fibrosarcoma HT-1080 tumor xenografts (∼1.5 ± 0.2% ID g −1 ). The tumor uptake of the two radiotracers was significantly reduced ( p < 0.05) in both animal models during blocking studies. The tumor-to-blood ratio was observed to be ∼2–2.5 for the two radiotracers, whereas the tumor-to-muscle ratio was significantly higher ( p < 0.005) for 68 Ga-HBED-CC-c(RGD) in the two animal models. The two radiotracers 68 Ga-HBED-CC-c(NGR) and 68 Ga-HBED-CC-c(RGD) exhibited renal excretion with rapid clearance from blood and other non-target organs. Thus, 68 Ga-chelated HBED-CC conjugated NGR and RGD peptides expressed features conducive towards development as tumor targeted molecular imaging probes. This study further opens avenues for the successful conjugation of different peptides with the acyclic chelator HBED-CC and expansion of 68 Ga-based radiopharmaceuticals.